2014
DOI: 10.1002/da.22229
|View full text |Cite
|
Sign up to set email alerts
|

GENDER-SPECIFIC ASSOCIATION OF VARIANTS IN THEAKR1C1GENE WITH DIMENSIONAL ANXIETY IN PATIENTS WITH PANIC DISORDER: ADDITIONAL EVIDENCE FOR THE IMPORTANCE OF NEUROSTEROIDS IN ANXIETY?

Abstract: These results suggest a modulatory effect of AKR1C1 activity on anxiety levels, most likely through changes in progesterone and allopregnanolone levels within and outside the brain. In summary, this is the first evidence for the gender-specific implication of the AKR1C1 gene in the expression of anticipatory anxiety in PD. Further analyses to unravel the functional role of the SNPs detected here and replication analyses are needed to validate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…Unlike estrogen, there are not extensive data documenting the specific neural systems regulated by progesterone, so it is difficult to propose neurobiological pathways. However, promising data suggest that progesterone may play an important regulatory role in gene expression within several systems (e.g., serotonin, Gamma-Amino Butyric acid) that are thought to be important in anxiety and/or depression (Arbo, Andrade, Osterkamp, Gomez, & Ribeiro, 2014; Bethea & Centeno, 2008; Bethea & Reddy, 2015; Lu, Eshleman, Janowsky, & Bethea, 2003; Quast et al, 2014; Schüle, Nothdurfterb, & Rupprecht, 2014). It is likely that progesterone activates genetic effects via the same mechanisms as those proposed for estrogen during puberty (e.g., differential production of neurotransmitters and/or their receptors), although this possibility awaits investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike estrogen, there are not extensive data documenting the specific neural systems regulated by progesterone, so it is difficult to propose neurobiological pathways. However, promising data suggest that progesterone may play an important regulatory role in gene expression within several systems (e.g., serotonin, Gamma-Amino Butyric acid) that are thought to be important in anxiety and/or depression (Arbo, Andrade, Osterkamp, Gomez, & Ribeiro, 2014; Bethea & Centeno, 2008; Bethea & Reddy, 2015; Lu, Eshleman, Janowsky, & Bethea, 2003; Quast et al, 2014; Schüle, Nothdurfterb, & Rupprecht, 2014). It is likely that progesterone activates genetic effects via the same mechanisms as those proposed for estrogen during puberty (e.g., differential production of neurotransmitters and/or their receptors), although this possibility awaits investigation.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A recent genome-wide copy number variation study also found an excess of common duplications in a region on 16p11.2. 15 Genome-wide association (GWA) studies of PD [11][12][13][14][15][16][17][18][19][20][21] have not yet established risk loci, though 1 genetic 12,14,22,23 and functional 12,22 data have recently implicated variation in TMEM132D.…”
Section: Introductionmentioning
confidence: 99%
“…Zwei der wichtigsten weiblichen Geschlechtshormone -Estradiol und Progesteron -übernehmen mit ihren Neurosteroiden wichtige modulierende Funktionen in serotonergen, dopaminergen und GA-BA-ergen Systemen (2)(3)(4)(5)(6)(7)(8). Eine Veränderung der peripheren Hormonkonzentrationen bzw.…”
Section: Discussionunclassified
“…Eine Veränderung der peripheren Hormonkonzentrationen bzw. der Relationen der Hormone untereinander, kann bei entsprechend disponierten Frauen zu einer Dysfunktionalität in den jeweiligen Transmittersystemen führen (2)(3)(4)(5)(6)(7)(8). Wieso manche Frauen hier besonders sensitiv sind und andere nicht, ist nicht bekannt.…”
Section: Discussionunclassified